2018
DOI: 10.1093/rheumatology/kex490
|View full text |Cite
|
Sign up to set email alerts
|

Systemic interferon type I and type II signatures in primary Sjögren’s syndrome reveal differences in biological disease activity

Abstract: Systemic IFN activation is associated with higher activity only in the ESSDAI biological domain but not in other domains or the total score. Our data raise the possibility that the ESSDAI biological domain score may be a more sensitive endpoint for trials targeting either IFN pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
99
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 44 publications
9
99
1
1
Order By: Relevance
“…The presence of an elevated expression of these genes is called an "IFN-signature". Systemic type I IFN signature is found in a large fraction of pSS patients [5]. The type I IFN signature has also been shown to be associated with presence of anti-SSA and anti-SSB antibodies, and hypergammaglobulinemia [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of an elevated expression of these genes is called an "IFN-signature". Systemic type I IFN signature is found in a large fraction of pSS patients [5]. The type I IFN signature has also been shown to be associated with presence of anti-SSA and anti-SSB antibodies, and hypergammaglobulinemia [5].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic type I IFN signature is found in a large fraction of pSS patients [5]. The type I IFN signature has also been shown to be associated with presence of anti-SSA and anti-SSB antibodies, and hypergammaglobulinemia [5]. Disease activity as evaluated by the European League Against Rheumatism (EULAR) Sjögren's syndrome disease activity index (ESSDAI) has been associated to type I IFN signature previously [6,7] although some studies fail to confirm the association [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although profiling of the blood transcriptome revealed a prevalent IFN type I signature in SLE, blocking the IFN pathway only showed efficacy in a subset of adult-onset SLE patients. Recent studies revealed that other gene signatures like IFN type I+II (M5.12), B cell, plasmablast and neutrophil signatures are important in SLE as well and some could be linked to specific clinical phenotypes [2,3]. Assessment of these novel gene signatures in SLE may help to distinguish specific disease phenotypes and guide treatment choices in the future.…”
mentioning
confidence: 99%